Diversifikasi Produk Arang Menjadi Biochar dan Asap Cair di Mitra Arang Sejahtera Jember - Harlianingtyas, Irma; Sugiyarto, Sugiyarto; Pratita, Dian Galuh; Cahyaningrum, Deltaningtyas Tri; Rohman, Hanif Fatur (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
The processing of organic waste into valuable and environmentally friendly products is a sustainable solution for small-scale businesses, such as Arang Sejahtera in Jember. This business produces charcoal from wood and agricultural waste; however, the combustion process generates smoke that is not utilized and may contribute to environmental pollution. This community service program aims to implement pyrolysis technology to produce biochar and liquid smoke as by-products. Pyrolysis technology not only enhances the efficiency of charcoal production but also reduces environmental impacts by converting the smoke generated into valuable products. Biochar can be used as an alternative fuel, soil amendment, and carbon sequestration agent, while liquid smoke has potential as a raw material for the chemical industry or liquid fertilizer. Through training and mentoring for Mitra Arang Sejahtera, it is expected that this initiative will improve productivity and result in more sustainable products, reduce air pollution, and provide greater economic benefits. This program also has the potential to be adopted by other SMEs in Jember and surrounding areas as a model for environmentally friendly biomass waste management.